2008
DOI: 10.1007/s00299-008-0510-4
|View full text |Cite
|
Sign up to set email alerts
|

Agroinfiltration of grapevine leaves for fast transient assays of gene expression and for long-term production of stable transformed cells

Abstract: Agrobacterium-mediated transient assays for the analysis of gene function are used as alternatives to genetic complementation and stable plant transformation. Although such assays are routinely performed in several plant species, they have not yet been successfully applied to grapevines. We explored genetic background diversity of grapevine cultivars and performed agroinfiltration into in vitro cultured plants. By combining different genotypes and physiological conditions, we developed a protocol for efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 28 publications
2
64
0
1
Order By: Relevance
“…[6][7][8][9][10] Agro-infiltration is a simple transformation process that exhibits highly efficient transformation and easy operation in several plant species including Arabidopsis, tobacco, grapevine, potato, switchgrass, and tomato. [9][10][11][12][13][14] In woody plants, several studies of transient gene expression by biolistic bombardment, protoplast transfection, and Agrobacterium co-cultivation in Populus have been reported, 15,16) while there is limited report on transient gene expression in mulberry.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] Agro-infiltration is a simple transformation process that exhibits highly efficient transformation and easy operation in several plant species including Arabidopsis, tobacco, grapevine, potato, switchgrass, and tomato. [9][10][11][12][13][14] In woody plants, several studies of transient gene expression by biolistic bombardment, protoplast transfection, and Agrobacterium co-cultivation in Populus have been reported, 15,16) while there is limited report on transient gene expression in mulberry.…”
mentioning
confidence: 99%
“…In grapevines, this technology has been recently applied to analyze the function of several genes such as VviAdh [75], VviPIP2 [76], VviCCD1 [77], and VviWRKY33 [78]. Likewise, this method has been proved to be very useful for transgenic complementation [79][80][81], technical studies [82][83][84][85][86][87], promoter analysis [88][89][90][91], subcellular localization analysis [92], and protein production [69,93] in grapevine. Nonetheless, the genetic background and plant growth conditions are key factors in performing successful Agrobacterium-mediated transformation.…”
Section: Indirect Gene Transfer Methods: Agrobacterium-mediated Transmentioning
confidence: 99%
“…The bacteria enter the intercellular air spaces within the leaf and transform a very large percentage of the internal mesophyll cells. The agroinjection method involves a needleless syringe that can be filled with the bacterial suspension and then pressed against the underside of a leaf to infiltrate the suspension by active pushing through the stomata [92]. This method can be used to rapidly and simply generate a chimeric plant, where a large number of leaf cells contain the gene of interest.…”
Section: Agroinjection and Agroinfiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transgenic plants were mainly acquired by Agrobacterium tumefaciens-mediated transformation and bombardment of embryo or callus via a desktop gene gun. In the process of Agrobacterium-mediated in planta transformation, the genotype is generally found to influence T-DNA transfer and transgene expression in Arabidopsis and grapevine [51][52][53][54] . Studies have reported in other plants species, the choice of the Agrobacterium strain appeared critical and specific because of specific host-bacteria inactions [52,55] .…”
Section: Discussionmentioning
confidence: 99%